2018
DOI: 10.15666/aeer/1606_76877697
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure and Potential Nitrogen Metabolisms of Subtropical Aquaculture Pond Microbiota

et al.

Abstract: Microorganisms play a substantial role in the aquatic nitrogen cycle. However, the community structures and metabolic potential of microbiota inhabiting subtropical aquaculture ponds are still poorly understood. In the present study, we investigated the community structure of pond microbiota by amplicons sequencing using the MiSeq sequencing platform and predicted their potential metabolic characteristics. A total of 614 dominant operational taxonomic units (OTUs) were detected from 27 samples, of which 61 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 33 publications
(42 reference statements)
4
32
0
Order By: Relevance
“…The accumulation of TN and TP in pond water is considered an important reason for slower growth rates in aquaculture (Rahman et al, 2005;Besson et al, 2016;Ni et al, 2018). In the present study, our results showed that TN and TP in pond water fluctuated but increased with increases in aquaculture time ( Fig.…”
Section: Discussionsupporting
confidence: 65%
“…The accumulation of TN and TP in pond water is considered an important reason for slower growth rates in aquaculture (Rahman et al, 2005;Besson et al, 2016;Ni et al, 2018). In the present study, our results showed that TN and TP in pond water fluctuated but increased with increases in aquaculture time ( Fig.…”
Section: Discussionsupporting
confidence: 65%
“…The mRNA primer sequences are listed in Table 2 , and RPL-17 was selected as a reference gene. Expression was calculated using the Ct (2 −ΔΔCt ) method [ 35 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…High-density culture in ponds not only reduces the growth rate of cultured fish, but also increases their FCR, and increases the accumulation of TN and TP in pond water and sediment (Rahman et al, 2005;Besson et al, 2016). The accumulation of TN and TP, and especially the increase in nitrite and ammonia nitrogen, will lead to the slow growth of cultured fish (Ni et al, 2018). In the present study, our results also showed that the growth rate of grass carp decreased gradually (Fig.…”
Section: Discussionmentioning
confidence: 99%